UPAYA PENGURANGAN RISIKO BENCANA MELALUI PELIBATAN PENYANDANG DISABILITAS DI INDONESIA: SEBUAH TINJAUAN KEPUSTAKAAN - Hayatul Khairul Rahmat; Ferra Puspito Sari; Mutiara Hasanah; Suandara Pratiwi; Achmad Muafi Ikhsan; R Rahmanisa; Syahti Pernanda; Adib Mahdi Fadil (Republic of Indonesia Defense University, 2020)
The disasters that occur not only have an impact on casualties and material damage and losses, but also raise the potential of the community to become persons with disabilities. Persons with disabilities in Indonesia are increasingly vulnerable because of the mismatch between disaster risk reduction efforts and the diverse needs of these groups. Therefore, it is very important to study disaster risk reduction efforts through the involvement of persons with disabilities in Indonesia to be more sensitive to the needs of each type of disability. This writing uses a library research method with a library approach. The involvement of persons with disabilities in disaster management activities will further ensure the fulfillment of the needs of persons with disabilities and their handling in the event of a disaster. However, it must be realized that the involvement of persons with disabilities in disaster management efforts is not an easy task, so it requires technical skills, knowledge and good faith from the parties involved. Mainstreaming of persons with disabilities in disaster risk reduction through effective programs and policies starting from the pre-disaster stage until after the disaster occurs according to the type of disability that exists.